The complete works of Peter Louis van Dijk : a short biography, annotated catalogue and discussion regarding gestures derived from ideology associated with the San people of the Southern Kalahari in three of his major works - Johnson, Alexander F. (University of Pretoria, 2017)
Thesis (DMus)--University of Pretoria, 2017.